Optimization of Dikmas Lantas by the Dikyasa Traffic Unit in Reducing High School Student Traffic Violations in the Garut Police Jurisdiction - Lintang, Janiar Arsyaddillah (Indonesian Journal of Police Studies, 2023)
This research is motivated by the level of student awareness about traffic in Garut Regency are still very low where many are affected by traffic raids. Activities that need to be done to minimize them include performing Traffic Community Education (Dikmas Lantas). Therefore study was conducted aimed at describe implementation of the Dikmas Lantas, influencing factors and solutions to optimize Dikmas Lantas activities in reducing violations of high school student traffic in Polres Garut. Theories and concepts used by writer are communication theory and management theory, and concepts are optimization, Concept of Community Education in the Field of Traffic,  Concept of Traffic Awareness, Concept of Traffic Violations. This study use descriptive qualitative analysis approach, in order to obtain an overview of the problems that occur, providing descriptive data in form of both verbal and written words obtained from information sources, so that the problem can be explored in depth. The results from this research obtained several conclusions about implementation of Dikmas Lantas in reducing traffict violations of high school student in Polres Garut by conducting direct socialization to high school students. Researcher concludes that influencing factors are internal factors which include personnel factors that should be equipped with vocational education, firmness of officers, police organizations, and facilities infrastructure. While external factors that weaken the role of the Traffic Unit are regional customs and community factors that have developed issue that ticketing sanctions can be resolved by peaceful means. Solution to optimize Dikmas Lantas activities by planning and coordinating between agencies.